Effects of Long-Term Feeding Flaxseed on Growth and Carcass Parameters, Ovarian Morphology and Egg Production of Pullets - Arshami, J.; Pilevar, M.; Elahi, M. (International Journal of Poultry Science, 2009)
The growth and reproduction performance and egg production parameters in 128 pullet chicks were monitored during 42 days received 5, 7.5 and 10% Flaxseed (FS) in their diet as a treatment. One-day-old Hy-line W-36 pullet chicks were divided into four groups of Control (C) and treatments (T1, T2 and T3) with 32 pieces in each one and 4 replicates. The chicks received ad libitum feed and water from the first day of age to week 22. Birds were individually penned from week 18 to determine time of oviposition and egg weight and quantity. The mean Body Weight (BW) and Feed Intake (FI) were recorded and calculated every 3 weeks. One pullet from each replicate on week 8 and day of oviposition was sacrified. Then, the weight of internal organs as percentage including: femur, FeW; breast, BrW; heart, HW; spleen, SW; liver, LW; gut, GW; fat cavity, FW; oviduct, ovary and Large Yellow Follicles (LYF) and number of LYF were measured. Our results indicated that as the level of FS increases from 5-7.5% and 10%, the BW and FI reduce, thus FCR increases in pullets. The evaluation of internal organs at 8th week and 1th oviposition, revealed no significant differences between treatments and control group. Although, in the 1st time, FS treatments increased HW and LW, but decreased FW; whereas in the 2nd time, FeW, BrW and GW induced and SW and LW reduced. Also, reproduction parameters showed reduction in weight of oviduct, ovary and LYF and number of LYF in treatment group. In addition, the weight of egg at oviposition, number of days to photo-stimulation and egg production on week 22 in T2 increased in birds received FS. Overall, the results indicated that feeding 7.5% of FS to pullets may produce more eggs than other treatments.